THE CONCENTRATION PATTERN AND IMPLICATION OF 2001 FLIGHT DEREGULATION POLICY ON DOMESTIC COMMERCIAL FLIGHT INDUSTRY IN INDONESIA - Istifadah, Nurul (Journal of Indonesian Economy and Business, 2009)
To enhance competition in the transport market, the Government of Indonesia has, since 2001, implemented deregulation policy for the flight sector. Through the decree of Minister of Transportation No. 11/2001, the requirements to obtain a flight operator license are simplified and an airline company can operate even without having to have its own plane.This research aims to analyze the condition before and after the flight deregulation policy. In particular, the purposes of this research are: (1) to analyze pattern of concentration for domestic commercial flight industry; (2) to calculate index of concentration for domestic commercial flight industry; (3) to analyze the market structureof domestic commercial flight industry; and (4) to analyze the implications of the flight deregulation policy in 2001. The measurement and analysis of the concentration pattern of domestic commercial flight industry are conducted using Hirschman-Herfindahl index, concentration ratio, and entropy index.The results show that the concentration level of domestic commercial flight industry in Indonesia is smaller under the new policy than that under the regulated regime. Not only the number of airline companies increases, but the share of domestic flight market is also more diversed. While the structure of domestic commercial flight market in Indonesia is still oligopoly, it changes from rigid into less rigid.Keywords: Concentration ratio; Hirschman-Herfindahl index; Entropy index; Domestic commercial flight industries; Flight deregulation policy.